EFL University Students’ Perceptions of Effective Teaching Grammar - Johari Afrizal; Arimuliani Ahmad; Intan Syazwina Salsabila (Journal of English Language and Education, 2021)
This research is taken to identify students’ perceptions of effective teaching grammar with 30 EFL university students as participants. Questionnaires, semi-structured interviews, and reflective notes were used to obtain data in this study.  Quantitative and qualitative analysis were used to analyse data, while data from interviews and reflective notes were transcribed. The results of this study showed that the students’ perception of effective teaching grammar in EFL indicated that students agree (96%) grammar is important for them. Most of the participants (more than 90%) prefer learning grammar through memorizing the rule of the language then followed by a set of examples. Other techniques have been mentioned namely listening to music, songs and poem. Learning by participating in real-life situations than developing their grammatical knowledge is also another technique that has been chosen.